Analysis of the Implementation of Minimum Laundry Service Standards Policy at RSUD R.Syamsudin,SH Sukabumi City: Study Of Decree of the Minister of Health of the Republic of Indonesia Number 129/Menkes/SK/II/2008 - Nitasari Nita; Darmo H Suwiryo; Ike Rachmawati (Dinasti International Journal of Education Management And Social Science, 2024)
KMK No. 129/Menkes/II/2008 concerning SPM Hospitals determines the indicators for laundry services in hospitals, namely the absence of incidents of lost linen and the timely provision of linen for inpatient rooms. At R. Syamsudin Regional Hospital, SH, the incidence of lost linen is still 7%, and the supply of inpatient room linen is often hampered. The research objective is to describe the implementation of the SPM laundry policy based on communication factors, resources, disposition and bureaucratic structure. This type of qualitative research with research results on the implementation of SPM laundry policies has not been effective, the policy is not yet known to implementers, human resources and equipment facilities are not optimal, the attitude of implementers is lacking but laundry implementers show high motivation in managing linen, SOPs are not appropriate, and supervision of linen in the wardroom accommodation is still lacking. It is necessary to communicate KMK policy no. 129/2008, ensuring that outsourced personnel and equipment repairs are prioritized. Excess working hours are given incentives according to applicable regulations, SOPs are made according to needs and the need for coordination with the inpatient room for monitoring linen in the room.